Lorem ipsum dolor sit amet, consectetur adipiscing elit. Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu. Fusce viverra neque at purus laoreet consequa. Vivamus vulputate posuere nisl quis consequat.

Create an accountLost your password? Please enter your username and email address. You will receive a link to create a new password via email.

3a + 5b = 26 ... (I)
a + 5b = 22 .... (II)
Let us write value of a in terms of b from equation (II) as
a = 22 - 5b ..... (III)
Substituting this value of 'a' in equation (I)
3(22 - 5b) + 5b = 26
? 3(22 - 5b) + 5b = 26
? 66 - 15b + 5b = 26
? 66 - 10b = 26
? -10b = 26 - 66
? -10b = -40
? b = 4
Substituting b = 4 in the equation (III)
a = 22 - 5b
? a = 22 - 5b (4)
? a = 22 - 20
? a = 2
a = 2, b = 4 is the solution

SÉå cÉUÉÇMüÉåÇ uÉÉsÉå UåZÉÏrÉ xÉqÉÏMüUhÉ
June 20 , 2018
0 Comments
208 views